Liposarcoma: experience in a tropical setting - Asuquo, Maurice; Nnoli, Martin; Nwagbara, Victor; Ashindoitiang, John; Ugbem, Theophilus; Akpan, Samuel (International Journal of Medicine, 2016)
Background: Virchow in 1860 described liposarcoma which arise from fat cells. It is a common soft tissue sarcoma found commonly in the limbs and retroperitoneum.Objectives: This study is an attempt to highlight the biographic indices, pattern, and challenges of management and outcomes of liposarcoma in a tropical setting and proffer solutions for improved outcome.Methods: Patients who presented to the University of Calabar Teaching Hospital from 2000-2014 with histologic diagnosis of liposarcoma were studied. This was compared with total soft tissue sarcoma and total malignancy seen during the same study period.Results: The 17 patients seen in the study period comprised 10 males and 7 females (M: F = 1.4:1) and their ages ranged from 37-70 years (mean 51 years). They accounted for 21.8% of soft tissue sarcoma and 0.9% of total malignancy. The commonest site involved was the lower limb 8(47%), while the abdomen ranked second 5(29%) with the retroperitoneum the commonest abdominal location. Pleomorphic liposarcoma was the commonest 8(47%) histologic type followed by myxoid 7(41%). The outcomes were generally poor with one hospital mortality. Sociocultural beliefs, ignorance and poverty were issues highlighted.Conclusions: Early presentation and diagnosis and treatment is advocated for improved outcome. Establishment of support groups in oncology will further provide health education services and compliment financing of treatment in view of the enormous cost of services and drugs.